HAK MENDAPATKAN PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS DALAM DIMENSI POLITIK HUKUM PENDIDIKAN - aprilia, wulan; Satriadi, Ari; mablin, rabia; qolbi, said; Andriani, Opi (Jurnal Pendidikan Vokasi dan Seni, 2025)
Countries are obligated to ensure that children with special needs (CWSN) have access to education as part of their human rights. This commitment is reflected in laws, regulations, and the implementation of inclusive education initiatives that prioritize equality and justice within the political and legal context of education. This study examines the challenges in realizing the right to education for children with disabilities and how Indonesia's educational politics and laws support this right. Insufficient funding, poor infrastructure, and a lack of awareness often hinder the implementation of educational rights for children with disabilities, even in the presence of laws such as Law No. 20 of 2003 on the National Education System and the Minister of Education Regulation on Inclusive Education